EVALUATION OF HOT MIX ASPHALT CONTAINING RECLAIMED ASPHALT PAVEMENT TO RESIST MOISTURE DAMAGE - Mohammed Qadir Ismael (Journal of Engineering and Sustainable Development, 2019)
Due to increasing cost of asphalt binder, significant economic savings can be realized by using the amount from reclaimed asphalt pavement (RAP) in the production of new hot mix asphalt (HMA). Moreover, this is an environmentally friendly option as it reduces the demand for virgin materials. It has to be remarked that in Iraq RAP is not used in the production of HMA and this valuable material is mostly degraded for use in lower value applications. Four mixtures were designed, which contains three different percent RAP, it is (0%, 5%, 15%) with asphalt grade (40-50) and (25%) with asphalt grade (60-70), it has been changed the grade of asphalt when adding RAP (25%) to compensate for the aged binder in the RAP when adding to mixture. All types of tests result demonstrated that all mixtures have good properties compared with the virgin mixture. This demonstrated that mixtures with RAP content could be successfully designed to meet the local volumetric and performance-specification requirements